Method for preparing layered gradient Ti2AlC0. 5N0. 5 through microwave molten salt
Through microwave molten salt pyrolysis method, rapid pyrolysis of organic fibers is used to provide C and N sources, which realizes the rapid preparation of MAX phase materials, solves the problems of long reaction time and uncontrollable morphology and structure in the prior art, and is suitable for large-scale industrial production.
Patent Information
- Application Number
- CN202411898539.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The reaction time during the preparation of existing MAX phase materials is long, the morphology and structure are uncontrollable, and it is difficult to meet the needs of large-scale industrial production.
The microwave molten salt pyrolysis method is used to provide C and N sources through rapid pyrolysis of organic fibers, and molten salt synthesis is carried out under microwave heating, so as to achieve the rapid preparation of hierarchical gradient structure MAX phase materials.
It realizes the rapid preparation of MAX phase materials, with high purity and stable reactions, and can control the morphology and structure at the same time, making it suitable for industrial production.
Smart Images

Figure CN119822337A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new material synthesis and preparation, and in particular to a method for preparing layered gradient Ti2AlC by microwave molten salt. 0.5 N 0.5 method. Background Art
[0002] MAX phase material is a ternary layered ceramic material with a hexagonal structure, in which M is a transition metal element, A is a main group element, and X is a C or N element. In the MAX phase material, the M-position atom and the X-position atom are connected by a strong covalent bond to form an MXM covalent bond, which has the advantages of high strength and elastic modulus, good thermal stability, small expansion coefficient, strong acid and alkali corrosion resistance, and good high-temperature oxidation resistance. On the other hand, the MX structure and the A atom are bonded by a weaker MA metal covalent bond, so that the MAX phase material has good processability while also having some characteristics of the A layer metal, such as electrical conductivity, thermal conductivity and ductility. Given the characteristics of MAX phase materials that combine the properties of ceramics and metals, MAX phase materials have great application potential in many high-tech fields such as aerospace, high-speed rail, nuclear industry, radar absorption and stealth.
[0003] At present, most of the research on the preparation of MAX phase materials at home and abroad is to mix the raw powders, cold press them into shape, and then sinter them at high temperature. This method is not suitable for the efficient and rapid preparation of MAX phase powder materials. Related literature reports that the morphology and type of MAX phase materials have a huge impact on their physical and chemical properties. CN202311651537 discloses a MAX phase material and its preparation method and application. Specifically, the M source and the X source are first mixed to prepare nanofibers by electrospinning and preheated for 2-12 hours to obtain a MX nanofiber precursor template, and then the MX precursor is mixed with the A source and heat treated at 1100-1600°C for 1-4 hours to obtain a MAX phase material. CN202410384549 discloses a high-purity gallium-based layered carbon / nitride MAX phase material and a preparation method thereof. First, metal powder M is mixed with graphite powder or metal nitride powder MN, and pre-calcined at 1200-1400°C to obtain an MX precursor. The MX precursor obtained is then infiltrated with molten metal Ga, and calcined at 1300-1600°C for 100-250 minutes to obtain a gallium-based layered carbon / nitride MAX phase material. These technologies add an additional N source to obtain carbon / nitride MAX phase materials, and require multiple steps of high-temperature treatment, and the reaction time is relatively long. The special morphology and structure have an important influence on the practical application of MAX phase materials. For example, in the field of electromagnetic wave absorption, morphology and structure regulation can promote the attenuation of electromagnetic wave incidence, so it is necessary to control the morphology and structure of MAX phase materials.
[0004] Therefore, it is crucial to develop a simple and efficient method that does not require the addition of additional C source and N source and can simultaneously control the morphology and structure of MAX phase materials, so as to meet the needs of mass production of high-quality carbonitride MAX phase materials. Summary of the invention
[0005] The purpose of the present invention is to provide a method for rapidly preparing a layered gradient structured MAX phase material by microwave molten salt pyrolysis, so as to solve the problems existing in the existing MAX phase material preparation process, such as long reaction time, uncontrollable morphology and structure, and difficulty in meeting large-scale industrial production.
[0006] In order to solve the above technical problems, the present invention adopts the following technical scheme: a microwave molten salt is used to prepare a layered gradient Ti2AlC 0.5 N 0.5 The method is characterized by comprising the steps of:
[0007] S1. Weigh Ti powder, Al powder, organic fiber, and inorganic salt in a mortar, add anhydrous ethanol, grind to obtain material a, and place material a in a ball mill until mixed to obtain material b;
[0008] S2. Rapidly dry material b in a microwave oven to remove anhydrous ethanol to obtain material c;
[0009] S3. The mixed material c is placed in a microwave oven under a protective atmosphere for molten salt synthesis, and selective microwave activation heating is performed to achieve rapid preparation of layered gradient carbonitride MAX phase materials;
[0010] S4. Take out the mixed material c after the reaction in S3, add 5 to 8 times the volume of the material of deionized water to remove inorganic salts, filter out the solid product, wash it repeatedly with deionized water and dry it, take the solid product and dry it to obtain a black powder, which is the layered gradient MAX phase material.
[0011] A further technical solution is that in step S1, the organic fiber is one or more of polyamide fiber, polyester fiber, polyacrylonitrile fiber, polypropylene fiber, and polyvinyl alcohol fiber, and the inorganic salt is one or two of NaCl and KCl.
[0012] A further technical solution is that in step S1, the molar ratio of Ti powder, Al powder, NaCl and KCl is (2-3):1:(1-4):(1-4), the amount of organic fiber is 1-5 g / molM-metal, the purity of Ti powder is 99%-99.99%, the purity of Al powder is 99%-99.99%, and the amount of anhydrous ethanol added is 200-400 ml / molM-metal.
[0013] A further technical solution is that in step S1, the rotation speed of the ball milling process is 300-400 r / min, and the ball milling time is 1-2 h.
[0014] A further technical solution is that in step S2, the microwave heating power is 600 W, the microwave frequency is 2450±50 MHz, and the heating time is 30 min.
[0015] A further technical solution is that in step S3, the reaction temperature is 1000-1100°C, the heating rate is 30-50°C / min, the insulation time is 10-30min, the microwave heating power is 4000-5000W, the microwave frequency is 2450±50 or 915±50MHz, and the protective atmosphere is argon or nitrogen.
[0016] A further technical solution is that the drying in step S4 is carried out using a blast drying oven, the drying temperature is 80-90° C., and the drying time is 30-60 min.
[0017] Reaction mechanism
[0018] Organic fiber pyrolysis → nitrogen-containing carbon fiber (N-CF)
[0019] Ti+N-CF→TiC 0.5 N 0.5
[0020] Ti+Al+TiC 0.5 N 0.5 →Ti2AlC 0.5 N 0.5
[0021] Weigh several of Ti powder, Al powder, organic fiber, and inorganic salt, and heat the organic fiber with microwave molten salt in one step to achieve pyrolysis of the organic fiber and preparation of MAX phase material at a relatively low temperature. Wash the product with deionized water to remove the inorganic salt, and dry the solid product after washing to obtain the MAX phase material. After pyrolysis, the organic fiber acts as a C source and a N source, and diffuses rapidly into the reaction system under the action of microwave and molten salt, and reacts with Ti to form a metal carbonitride intermediate phase. The metal carbonitride further reacts with Al to obtain a carbonitride MAX phase material. By controlling the reaction time, the Ti2AlC 0.5 N 0.5 / TiC 0.5 N 0.5 Preparation of layered gradient structure MAX phase material with cavity / amorphous carbon / microcrystalline carbon. The present invention prepares layered gradient Ti2AlC by microwave molten salt 0.5 N 0.5The method is used to prepare layered gradient MAX phase materials. The product has high purity, stable and efficient reaction, and can simultaneously achieve control of the morphology and composition of the MAX phase materials. The method is simple, efficient, and easy to industrialize.
[0022] Compared with the prior art, the invention has the following beneficial effects: using microwave heating, the organic fiber is rapidly pyrolyzed to provide C source and N source and the temperature is rapidly raised, so that the inorganic salts and the like quickly enter the molten state, providing a uniform polar liquid phase environment for the reaction, thereby reducing the activation energy of the reaction. After pyrolysis, the organic fiber is used as a C source and a N source, and as a template, with the diffusion of C and N elements, the Ti2AlC 0.5 N 0.5 / TiC 0.5 N 0.5 / cavity / amorphous carbon / microcrystalline carbon layered gradient strong wave absorption MAX phase material preparation. No additional N source and C source are needed, and the layered gradient structure and morphology can be precisely controlled by reaction time. The reaction is carried out under a protective atmosphere. The layered gradient structure of the MAX phase material has obvious characteristics. The entire process is safe, efficient, clean, environmentally friendly, and low energy consumption, suitable for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The Ti2AlC obtained in Example 1 0.5 N 0.5 SEM electron microscope image.
[0024] Figure 2 The Ti2AlC obtained in Example 1 0.5 N 0.5 Cross-sectional SEM electron microscope image.
[0025] Figure 3 The Ti2AlC obtained in Example 3 0.5 N 0.5 Cross-sectional SEM electron microscope image.
[0026] Figure 4 The Ti2AlC obtained in Examples 1-3 0.5 N 0.5 XRD pattern of .
[0027] Figure 5 The Ti2AlC obtained in Example 1 0.5 N 0.5 Electromagnetic wave absorption performance diagram. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0029] Example 1
[0030] The raw materials were weighed according to the amounts of 19.14 g Ti powder, 2.69 g Al powder, 2 g polyacrylonitrile fiber, 46.7 g NaCl, and 59.6 g KCl.
[0031] (1) First, the above raw materials were placed in a mortar, and 150 ml of anhydrous ethanol was added to grind to obtain material a. Material a was placed in a ball mill and ball milled at 300 r / min for 1 h until mixed evenly to obtain material b.
[0032] (2) Material b was quickly dried in a microwave oven to remove anhydrous ethanol. The microwave power was 600 W, the microwave frequency was 2450±50 MHz, and the heating time was 30 minutes to obtain material c.
[0033] (3) Material c was transferred to a microwave oven under an argon atmosphere for molten salt synthesis, with a reaction temperature of 1000°C, a microwave power of 4500W, a microwave frequency of 2450±50MHz, a heating rate of 30°C / min, and a holding time of 10min.
[0034] (4) The reactant was taken out, and deionized water 8 times the volume of the material was added to remove inorganic salts, and the solid product was filtered out, and was repeatedly washed with deionized water and then dried. The drying was carried out in a forced air drying oven at a drying temperature of 90° C. and a drying time of 45 min to obtain a treated reaction product.
[0035] Example 2
[0036] The raw materials were weighed according to the amounts of 19.14 g Ti powder, 2.69 g Al powder, 2 g polyacrylonitrile fiber, 46.7 g NaCl, and 59.6 g KCl.
[0037] (1) First, the above raw materials were placed in a mortar, and 150 ml of anhydrous ethanol was added to grind to obtain material a. Material a was placed in a ball mill and ball milled at 300 r / min for 1 h until mixed evenly to obtain material b.
[0038] (2) Material b was quickly dried in a microwave oven to remove anhydrous ethanol. The microwave power was 600 W, the microwave frequency was 2450±50 MHz, and the heating time was 30 minutes to obtain material c.
[0039] (3) Material c was transferred to a microwave oven under an argon atmosphere for molten salt synthesis, with a reaction temperature of 1000°C, a microwave power of 4500 W, a microwave frequency of 2450±50 MHz, a heating rate of 30°C / min, and a holding time of 20 min.
[0040] (4) The reactant was taken out, and deionized water 8 times the volume of the material was added to remove inorganic salts, and the solid product was filtered out, and was repeatedly washed with deionized water and then dried. The drying was carried out in a forced air drying oven at a drying temperature of 90° C. and a drying time of 45 min to obtain a treated reaction product.
[0041] Example 3
[0042] The raw materials were weighed according to the amounts of 19.14 g Ti powder, 2.69 g Al powder, 2 g polyacrylonitrile fiber, 46.7 g NaCl, and 59.6 g KCl.
[0043] (1) First, the above raw materials were placed in a mortar, and 150 ml of anhydrous ethanol was added to grind to obtain material a. Material a was placed in a ball mill and ball milled at 300 r / min for 1 h until mixed evenly to obtain material b.
[0044] (2) Material b was quickly dried in a microwave oven to remove anhydrous ethanol. The microwave power was 600 W, the microwave frequency was 2450±50 MHz, and the heating time was 30 minutes to obtain material c.
[0045] (3) Material c was transferred to a microwave oven under an argon atmosphere for molten salt synthesis, with a reaction temperature of 1000°C, a microwave power of 4500 W, a microwave frequency of 2450±50 MHz, a heating rate of 30°C / min, and a holding time of 30 min.
[0046] (4) The reactant was taken out, and deionized water 8 times the volume of the material was added to remove inorganic salts, and the solid product was filtered out, and was repeatedly washed with deionized water and then dried. The drying was carried out in a forced air drying oven at a drying temperature of 90° C. and a drying time of 45 min to obtain a treated reaction product.
[0047] Example 4
[0048] The raw materials were weighed according to the amounts of 28.7 g Ti powder, 2.69 g Al powder, 4 g polyester fiber, 46.7 g NaCl, and 59.6 g KCl.
[0049] (1) First, the above raw materials were placed in a mortar, and 150 ml of anhydrous ethanol was added to grind to obtain material a. Material a was placed in a ball mill and ball milled at 300 r / min for 2 h until mixed evenly to obtain material b.
[0050] (2) Material b was quickly dried in a microwave oven to remove anhydrous ethanol. The microwave power was 600 W, the microwave frequency was 2450±50 MHz, and the heating time was 30 minutes to obtain material c.
[0051] (3) Material c was transferred to a microwave oven under an argon atmosphere for molten salt synthesis, with a reaction temperature of 1050°C, a microwave power of 5000 W, a microwave frequency of 2450±50 MHz, a heating rate of 40°C / min, and a holding time of 30 min.
[0052] (4) The reactant was taken out, and deionized water 8 times the volume of the material was added to remove inorganic salts, and the solid product was filtered out, and was repeatedly washed with deionized water and then dried. The drying was carried out in a forced air drying oven at a drying temperature of 90° C. and a drying time of 45 min to obtain a treated reaction product.
[0053] The present invention prepares layered gradient Ti2AlC by a microwave molten salt 0.5 N 0.5 method, Figure 1 Ti2AlC was prepared in Example 1 0.5 N 0.5 The scanning electron microscope shows that the product retains a fibrous morphology; Figure 2 Ti2AlC was prepared in Example 1 0.5 N 0.5 Cross-sectional SEM electron microscope image, the product is Ti2AlC 0.5 N 0.5 / TiC 0.5 N 0.5 / cavity / amorphous carbon / microcrystalline carbon hierarchical gradient structure; Figure 3 Ti2AlC was prepared in Example 3 0.5 N 0.5 Cross-sectional SEM electron microscope image, the product is Ti2AlC 0.5 N 0.5 / TiC 0.5 N 0.5 / Cavity layered hollow tubular structure. Figure 4 For Example 1-3, Ti2AlC 0.5 N 0.5 From the XRD diagram, it can be seen that the product has high purity and the reaction is stable. Figure 5 Ti2AlC is obtained for Example 1 0.5 N 0.5 The electromagnetic wave absorption performance diagram shows that the product exhibits super strong electromagnetic wave absorption performance. This proves that by adopting this method, by controlling the reaction time, the number of layers and the gradient structure of the layered gradient MAX phase material can be effectively controlled, which has great advantages in preparation efficiency and reaction stability. It can realize the efficient and rapid preparation of high-quality MAX phase materials to meet the needs of different fields such as aerospace, energy catalysis, and electromagnetic wave absorption.
[0054] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. Preparation of layered gradient Ti2AlC by microwave molten salt 0.5 N 0.5 The method is characterized in that The steps include: S1. Weigh Ti powder, Al powder, organic fiber, and inorganic salt in a mortar, add anhydrous ethanol, grind to obtain material a, and place material a in a ball mill until mixed to obtain material b; S2. Rapidly drying material b in a microwave oven to remove anhydrous ethanol to obtain material c; S3. The mixed material c is placed in a microwave oven under a protective atmosphere for molten salt synthesis, and selective microwave activation heating is performed to achieve rapid preparation of layered gradient carbonitride strong absorbing MAX phase material; S4. Take out the mixed material c after the reaction in S3, add 5 to 8 times the volume of the material of deionized water to remove inorganic salts, filter out the solid product, wash it repeatedly with deionized water and dry it, take the solid product and dry it to obtain a black powder, which is the layered gradient MAX phase material.
2. Preparation of layered gradient Ti2AlC by microwave molten salt according to claim 1 0.5 N 0.5 The method is characterized in that: In step S1, the organic fiber is one or more of polyamide fiber, polyester fiber, polyacrylonitrile fiber, polypropylene fiber, and polyvinyl alcohol fiber, and the inorganic salt is one or two of NaCl and KCl.
3. Preparation of layered gradient Ti2AlC by microwave molten salt according to claim 1 0.5 N 0.5 The method is characterized in that: In step S1, the molar ratio of Ti powder, Al powder, NaCl and KCl is (2-3):1:(1-4):(1-4), the amount of organic fiber used is 1-5 g / mol M-site metal, the purity of Ti powder is 99%-99.99%, the purity of Al powder is 99%-99.99%, and the amount of anhydrous ethanol added is 200-400 ml / mol M-site metal.
4. Preparation of layered gradient Ti2AlC by microwave molten salt according to claim 1 0.5 N 0.5 The method is characterized in that: In the step S1, the rotation speed of the ball milling process is 300-400 r / min, and the ball milling time is 1-2 h.
5. Preparation of layered gradient Ti2AlC by microwave molten salt according to claim 1 0.5 N 0.5 The method is characterized in that: In step S2, the microwave heating power is 600 W, the microwave frequency is 2450±50 MHz, and the heating time is 30 min.
6. Preparation of layered gradient Ti2AlC by microwave molten salt according to claim 1 0.5 N 0.5 The method is characterized in that: In step S3, the reaction temperature is 1000-1100° C., the heating rate is 30-50° C. / min, the insulation time is 10-30 min, the microwave heating power is 4000-5000 W, the microwave frequency is 2450±50 or 915±50 MHz, and the protective atmosphere is argon or nitrogen.
7. Preparation of layered gradient Ti2AlC by microwave molten salt according to claim 1 0.5 N 0.5 The method is characterized in that: In step S4, the drying is performed in a blast drying oven at a drying temperature of 80 to 90° C. for a drying time of 30 to 60 minutes.
Citation Information
Patent Citations
Preparation method of sulfur-doped graphite-phase carbon nitride microtubes
CN113443612A
Method for recycling carbon fibers by microwave molten salt concerted catalysis treatment of carbon fiber composite material
CN115873301A
Two-dimensional carbon nitride material and method of preparation
US20170240422A1
"MXene" PARTICULATE MATERIAL, PRODUCTION PROCESS FOR THE SAME AND SECONDARY BATTERY
US20200255343A1
Process of obtaining zeolite catalysts containing metal by microwave- and ultrasonic-assisted hydrothermal synthesis
WO2021107801A1